Growth Inhibiting Activity Of Staphylococcus Aureus ATCC 25923 Kirinyuh Leaves (Chromolaena Odorata L.) Using The Soxhletation Method - Fitriawati, Anna; Rahmad Adji, Alenda; Ardiyantoro, Bagas; Abdul Wahab Sabrina, Azimah; Karim, Karim (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2024)
Kirinyuh leaves (Chromolaena odorata L.) have the potential as a medicinal plant because of the active compounds contained in kirinyuh leaves (Chromolaena odorata L.). The purpose of this study was to determine the antibacterial activity of ethanol extract of kirinyuh leaves (Chromolaena odorata L.) against the growth of Staphylococcus aureus ATCC 25923 bacteria. Kirinyuh leaf extract (Chromolaena odorata L.) was carried out using the soxhletation method and the solvent used was 96% ethanol. The concentrations used for each treatment were 30%, 40% and 50%. Each concentration was tested for antibacterial activity against Staphylococcus aureus bacteria using the disc diffusion method. The results showed that the extract of kirinyuh leaves (Chromolaena odorata L.) with a concentration of 30% had an average diameter of the inhibition zone of 9.2 mm, a concentration of 40% had an average diameter of the inhibition zone of 12.36 mm, and a concentration of 50% had an average diameter of the inhibition zone of 13.71 mm. The research conducted can be concluded that the extract of kirinyuh leaves can provide the best effect of inhibiting bacterial growth at a concentration of 50% with the results of the anova test p <0.05 which means there is a significant difference compared to other concentrations